MR Angiography of the Body - Neri, E.; Cosottini, M.; Caramella, D.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Magnetic resonance angiography (MRA) continues to undergo exciting technological advances that are rapidly being translated into clinical practice. It also has evident advantages over other imaging modalities, including better patient safety compared with CT angiography and superior accuracy and contrast resolution compared with ultrasonography. With the aid of numerous high-quality illustrations, this book reviews the current role of MRA of the body. It is divided into three sections. The first section is devoted to issues relating to image acquisition technique and sequences. Individual chapters focus on flow-based MRA, contrast media, contrast-enhanced MRA, artifacts, and image processing. The second and principal section of the book addresses the clinical applications of MRA in various parts of the body, including the neck vessels, the spine, the thoracic aorta and pulmonary vessels, the heart and coronary arteries, the abdominal aorta and renal arteries, and peripheral vessels. The role of the blood pool contrast agents for the diagnosis and characterization of vascular disease is fully explored. The final section considers the role of MRA in patients undergoing liver or pancreas and kidney transplantation. This book will be an invaluable aid to all radiologists who work with MRA.
Image Acquisition Technique and Sequences -- Flow-Based MRA -- MR Angiography Contrast Agents -- Image Acquisition Technique and Sequences Contrast-Enhanced MRA -- Artifacts in MR-Angiography -- Image Processing -- Clinical Applications -- Radiologic Vascular Anatomy -- Neck Vessels -- Thoracic Aorta and Pulmonary Vessels -- Heart and Coronary Arteries -- Abdominal Aorta and Renal Arteries -- Peripheral Vessels -- Special Topics: Transplants -- MRA in Liver and in Orthotopic Liver Transplants -- MRA in Transplanted Pancreas and Kidneys.
Keywords: Medicine; Radiology, Medical; Internal medicine; Angiography; Cardiology; Transplantation of organs, tissues, etc; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Angiology; Internal Medicine; Cardiology; Transplant Surgery